Violence in the print media: towards a psychosocial perspective - Djamila OUCHENE (Eon)
This study examines the impact of sports-specific print media on violence in football stadiums in Algeria. The goal is to analyze the relationship between media discourse and violent behaviors observed, particularly among young spectators. A quantitative approach was adopted, with a questionnaire distributed to 140 sports journalists from four Algerian newspapers. The questions focused on sports media and violence. The results show that the sports press plays a crucial role in inciting violence by cultivating a culture of revenge and reinforcing fanaticism among supporters. Media coverage seems to amplify the portrayal of violence, contributing to the escalation of violent behaviors in the stadiums. The study highlights the influence of media on young people, increasing their tendency to adopt aggressive behaviors, which raise concerns regarding the harmful effect of these media representations on society. The conclusions suggest that media should adopt a more responsible approach to limit the spread of violence in sports and in the Algerian society.